Cognitive neuropsychological functioning in New Zealand Māori diagnosed with schizophrenia. (June 2016) - Kake, Tai R; Garrett, Nicholas; Te Aonui, Menetta
Objective: Previous research suggests that New Zealand Māori may have an elevated rate of schizophrenia. However, there is limited evidence on important clinical features of the illness in this population. This study examined cognitive neuropsychological functioning in 54 adult Māori diagnosed with schizophrenia and 56 Māori controls. This study also examined associations between cognition, medication and symptoms of psychosis in the schizophrenia group. Method: The groups were matched on socio-demographic variables, handedness and premorbid cognitive ability. Participants were assessed on neuropsychological tests of attention, executive ability, motor, premorbid ability, verbal/non-verbal memory and verbal fluency (English/Māori versions). The Positive and Negative Syndrome Scale was used to assess psychotic symptoms. Information on cultural identity, duration of illness, duration of untreated psychosis, medication and substance abuse was collected. Results: The performance of the schizophrenia group was significantly lower than the control group on all the neuropsychological tests, except the test of attention. The effect sizes were moderate to large: 0.78 for motor function; 1.3 for executive ability, verbal fluency and visual memory; 1.6 for verbal learning and 1.8 for verbal memory. These differences remained after adjustment for multiple comparisons and covariates. A higher dose of antipsychotic medication and a higher anticholinergic load were associated with greater verbal memory impairment ( r  = −0.38 and r  = −0.38, respectively). A longer duration of illness was associated with greater impairment of verbal memory (rho = −0.48), verbal learning (rho = −0.41) and visual memory (rho = −0.44). Conclusion: The findings for the schizophrenia group show a profile of generalised cognitive impairment with greater impairment of verbal memory. The cognitive impairment in this group was independent of psychotic symptoms, but was associated with a higher antipsychotic dose, higher anticholinergic load and longer duration of illness. These findings have implications for clinical prescribing practices and rehabilitation for New Zealand Māori diagnosed with schizophrenia.